Evaluating Green Behavior Index in Vocational Education for Sustainable Campus Development - Warju, Warju; Köhler, Thomas; Ariyanto, Sudirman; Komarudin, Komarudin (Journal of Technical Education and Training, 2026)
Vocational education plays a strategic role in supporting sustainable development, particularly through the establishment of environmentally conscious campuses. Although various sustainability initiatives have been implemented in higher education institutions, structured measurement of student behavior remains limited. This study evaluates the application of the Green Behavior Index (GBI) as a behavioral measurement tool while assessing environmental behavior in a vocational education context. The instrument covers six key dimensions: energy use, waste management, water conservation, carbon emissions, healthy lifestyles, and fuel consumption. A quantitative survey method was employed, involving 1,018 respondents consisting of students, lecturers, and educational staff. The minimum sample size was determined using the Slovin formula, and data were collected through a voluntary response sampling method using an online questionnaire distributed via Google Forms. Data were analyzed using descriptive statistics and inferential tests, including analysis of variance and advanced comparisons. The results indicate that respondents, particularly students, exhibit strong environmentally friendly behaviors in routine aspects, such as energy conservation and sanitation, but remain weak in behaviors that require systemic efforts, including emission control and participation in environmental programs. No significant influence of demographic factors was found, indicating that internal and contextual factors have a greater impact on differences in behavior. These findings provide an empirical basis for developing more effective and personalized sustainability policies in vocational education. Improvements to the behavioral measurement tool are also recommended to capture the complexity of sustainable practices across different groups within the academic community.